Comparison of QT Interval between Neonates with Maternal Gestational Diabetes and Healthy Mothers - Hassan Esmaeili; Maryam Koochaki; Mahsa Besharat; Farzad Sharifnezhad; Ehsan Alaee (Mashhad University of Medical Sciences, 2021)
Background: The risk of developing metabolic syndrome and diseases, such as diabetes mellitus, has been increased as a worldwide rise in obesity. Gestational diabetes mellitus (GDM) or maternal hyperglycemia is a risk factor for cardiac dysfunction in neonates. The present study compared the QT interval in neonates with maternal GDM and healthy mothers. Methods: This case-control study was carried out on term neonates with maternal GDM (case group; n=42) and healthy non-diabetic mothers (control group; n=42) in Sayyad-e-Shirazi hospital in Gorgan, Northeast of Iran, within March 2016 and February 2017. A pediatric cardiologist evaluated septal hypertrophy by Doppler echocardiography (Zonare ZS3) during the first 2 weeks after birth. A standard 12-lead electrocardiogram was recorded for 10 sec, and a corrected QT (QTc) value was calculated. The data were analyzed by the latest version of SPSS software (version 16) using the Chi-square and t-test for the assessment of the differences in the QT values and other indices between the two groups. P-values less than 0.05 were considered statistically significant. Results: The results of the present study showed congenital heart diseases (CHDs) in six neonates. Significantly higher QT (249±36 and 245± 28 ms), septal thickness (6.09±1.07 and 5±1 mm), and lower QTc value (382±44.06 and 392± 34 ms) were observed in the case group, compared to those reported for the control group (p <0.001). The QTc dispersion was significantly different between the subjects under insulin therapy and participants receiving an antihyperglycemic oral regimen. Conclusion: In this study, significant thicker cardiac septum and higher QT interval were observed in the neonates born from mothers with GDM in comparison to those from healthy mothers. This could suggest close cardiac monitoring of these neonates due to the higher probability of CHDs.